DNA Damage, Cell Cycle Arrest, and Apoptosis Induction Caused by Lead in Human Leukemia Cells - Yedjou, Clement G. (Int J Environ Res Public Health, 2015)
In recent years, the industrial use of lead has been significantly reduced from paints and ceramic products, caulking, and pipe solder. Despite this progress, lead exposure continues to be a significant public health concern. The main goal of this research was to determine the in vitro mechanisms of lead nitrate [Pb(NO(3))(2)] to induce DNA damage, apoptosis, and cell cycle arrest in human leukemia (HL-60) cells. To reach our goal, HL-60 cells were treated with different concentrations of Pb(NO(3))(2) for 24 h. Live cells and necrotic death cells were measured by the propidium idiode (PI) assay using the cellometer vision. Cell apoptosis was measured by the flow cytometry and DNA laddering. Cell cycle analysis was evaluated by the flow cytometry. The result of the PI demonstrated a significant (p < 0.05) increase of necrotic cell death in Pb(NO(3))(2)-treated cells, indicative of membrane rupture by Pb(NO(3))(2) compared to the control. Data generated from the comet assay indicated a concentration-dependent increase in DNA damage, showing a significant increase (p < 0.05) in comet tail-length and percentages of DNA cleavage. Data generated from the flow cytometry assessment indicated that Pb(NO(3))(2) exposure significantly (p < 0.05) increased the proportion of caspase-3 positive cells (apoptotic cells) compared to the control. The flow cytometry assessment also indicated Pb(NO(3))(2) exposure caused cell cycle arrest at the G(0)/G(1) checkpoint. The result of DNA laddering assay showed presence of DNA smear in the agarose gel with little presence of DNA fragments in the treated cells compared to the control. In summary, Pb(NO(3))(2) inhibits HL-60 cells proliferation by not only inducing DNA damage and cell cycle arrest at the G(0)/G(1) checkpoint but also triggering the apoptosis through caspase-3 activation and nucleosomal DNA fragmentation accompanied by secondary necrosis. We believe that our study provides a new insight into the mechanisms of Pb(NO(3))(2) exposure and its associated adverse health effects.